Deber de prevención del daño. Acción preventiva. Causalidad - Lamanna Guiñazú, Emiliano C. (2012)
Fil: Lamanna Guiñazú, Emiliano C. Pontificia Universidad Católica Argentina. Facultad de Derecho; Argentina